2003
DOI: 10.1021/bm0300406
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme−Lysozyme and Lysozyme−Salt Interactions in the Aqueous Saline Solution:  A New Square-Well Potential

Abstract: We investigate lysozyme-lysozyme and lysozyme-salt interactions in electrolyte solutions using a molecular-thermodynamic model. An equation of state based on the statistical mechanical perturbation theory is applied to describe the interactions. The perturbation term includes a new square-well potential of mean force, which implies the information about the lysozyme surface and salt type. The attractive energy of the potential of mean force is correlated with experimental cloud-point temperatures of lysozyme i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The influence of salts on polymers is quite well understood and is mainly due to the screening of electrostatic interactions by salt ions and the Donnan effect [25]. Many studies have shown that the magnitude of various salt effects varies according to the lyotropic or Hofmeister series.…”
Section: Effect Of the Ionic Strengthmentioning
confidence: 99%
“…The influence of salts on polymers is quite well understood and is mainly due to the screening of electrostatic interactions by salt ions and the Donnan effect [25]. Many studies have shown that the magnitude of various salt effects varies according to the lyotropic or Hofmeister series.…”
Section: Effect Of the Ionic Strengthmentioning
confidence: 99%
“…In practice, the simple square-well potential or Yukawa potential is adopted to describe the interactions between two globular protein molecules in an electrolyte solution. When the square-well potential is used, the energy parameter in the square-well potential needs to be represented as a function of ionic strength [10]. The hard-core two-Yukawa potential has been used to correlate and predict the osmotic pressures and diffusion coefficients of globular protein in electrolyte solutions [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…18 Similarly, the ionic strength effect on electrostatic interactions is known as that electrostatic interactions between proteins decrease as ionic strength increases. 19,20 In contrast, the strength of hydrophobic bonds is enhanced by increasing the salt concentration. 21 In protein structures, hydrogen bonds, electrostatic attractions, and hydrophobic bonds have similar binding strengths, while the van der Waals forces are much weaker, making a relatively small contribution to protein-protein binding.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Goto reported 24 that the accessible hydrophobic surface areas that are buried between the enzyme and the primary contact step are proportional to their experimental binding energies, indicating that the hydrophobic interaction strongly drives enzyme-protein binding. Generally, the proteinprotein mutual-binding force/energy that is due to non-covalent interactions depends largely on the salt concentration of the solution, [18][19][20][21][22] and protein-protein mutual-binding energy increases with the salt concentration. 19,21 In the present study, the reversibility of antigen-antibody binding decreased as the ionic strength increased.…”
Section: Resultsmentioning
confidence: 99%